Issues of Increasing the Efficiency of Investment and Innovation Activities of Enterprises - Gafurova Umida Fatikhovna (Genius Journals, 2022)
The article examines the theoretical and methodological basis of the processes associated with the role of foreign investment in ensuring the competitiveness of national enterprises. Cases related to the role of foreign investment in ensuring the competitiveness of national enterprises were assessed. The impact of existing shortcomings and problems on the country’s competitiveness has been studied. Scientific proposals and practical recommendations have been developed to improve the processes related to the role of foreign investment in ensuring the competitiveness of national enterprises. It also examines the views of foreign economists on the impact of the investment climate on business
Keywords: Investment Climate; Foreign Investment; Investment Activity; Investment Policy